When the silence breaks: Delayed symptomatic arrhythmia emerging years after tetralogy of fallot repair — A case report - Mulawarman, Rido; Dony Yugo Hermanto; Siagian, Sisca (Universitas Brawijaya, 2026)
Background: Surgical repair of Tetralogy of Fallot (TOF) has markedly improved long-term survival in congenital heart disease patients. However, late-onset arrhythmias remain a significant cause of morbidity and can lead to sudden cardiac death. Case summary: We report a 9-year-old boy with a history of complete TOF repair using a transannular patch at the age of 2 years, who presented with recurrent syncope and seizure-like episodes several years postoperatively. Neurological investigations, including brain MRI and electroencephalography, were unremarkable, leading to an initial misdiagnosis of epilepsy. Despite antiepileptic therapy, symptoms persisted. Subsequent 24-hour Holter monitoring demonstrated a high burden of polymorphic premature ventricular complexes (PVCs), non-sustained ventricular tachycardia (NSVT), and episodes of junctional rhythm with chronotropic incompetence. Initiation of oral verapamil resulted in complete resolution of symptoms. An electrophysiological study (EPS) is planned to further characterize the arrhythmic substrate and guide potential definitive intervention. Conclusion: This case emphasizes that late-onset ventricular arrhythmias can occur years after anatomically successful TOF repair and may mimic neurological disorders, delaying accurate diagnosis. Early recognition of arrhythmic mechanisms and timely referral for EPS are essential to optimize management, avoid inappropriate therapy, and mitigate the risk of sudden cardiac death.